Effect of exopolysaccharide-producing Azotobacter and cow manure on nutrient uptake and root-to-shoot ratio of sorghum - Reginawanti Hindersah; Anny Yuniarti; Hidiyah Ayu Ratna Ma’rufah (Universitas Lancang Kuning, 2021)
Nitrogen-fixing Azotobacter synthesizes exopolysaccharide, which is important among other to improve aggregate stability and hence nutrients uptake. A pot experiment has been conducted to determine the effect of exopolysaccharide-producing Azotobacter and organic matter on nitrogen, phosphor, and potassium uptake by the shoot of sorghum (Sorghum bicolor (L.) Moench), and plant growth. The pot experiment was setup in randomized block design which test eight combination treatments of Azotobacter isolates (AS5, AS6, and AS5 + AS6) and organic matter application (with and without 20 t ha-1 of cow manure). The result showed dual inoculation of Azotobacter AS5 and AS6 inoculation combined with cow manure application increased N and P uptake. The dual inoculation treatment did not affect root length; but increased the shoot height and dry weight when accompanied by the application of cow manure. The ratio of root and shoot dry weight was not influenced by single or dual Azotobacter inoculation with or without organic matter.